Development and evaluation of Goal setting and Action Planning (G-AP) training to support person-centred rehabilitation practice - Scobbie, Lesley; Elliott, Katie; Boa, Sally; Grayson, Lynn; Chesnet, Emily; Izat, Iona; Barber, Mark; Fisher, Rebecca (Frontiers in Rehabilitation Sciences, 2025)
BackgroundStroke survivor's goals reflect their individual priorities and hopes for the future. Person-centred goal setting is recommended in rehabilitation clinical guidelines, but evidence-based training to support its implementation in practice is limited. We aimed to develop, describe and evaluate a new Goal setting and Action Planning (G-AP) rehabilitation training resource to support person-centred goal setting practice in community neuro-rehabilitation settings.MethodsA clinical-academic team, advisory group and web-design company were convened to co-develop the G-AP training resource. G-AP training was then delivered to multi-disciplinary staff (n = 48) in four community neuro-rehabilitation teams. A mixed methods evaluation utilising a staff questionnaire and focus group discussion was conducted to investigate staff experiences of G-AP training and their early G-AP implementation efforts. Questionnaire data were analysed descriptively; focus group data were analysed using a Framework approach. An integrated conceptual overview of data was developed to illustrate findings.ResultsA fully online G-AP training resource comprising a training website and two interactive webinars was developed. Following training, 41/48 (85%) staff completed the online questionnaire and 8/48 (17%) participated in the focus group. Nearly all staff rated the training website as excellent (n = 25/40; 62%) or good (n = 14/40; 35%) and the webinars as excellent (n = 26/41; 63%) or good (n = 14/41; 34%). Following training, staff agreed they were knowledgeable about G-AP (37/41; 90%) and had the confidence (35/40; 88%) and skills (35/40; 88%) to use it in practice. Within one month of training, staff described implementing G-AP individually, but transitioning to implementation at a team level required more time to develop new working practices. Team context including staff beliefs about G-AP, leadership support and competing demands impacted (positively and negatively) on staff training engagement, learning experience and implementation efforts.ConclusionsThe new G-AP training resource was positively evaluated and supported early G-AP implementation efforts. This study advances our understanding of training evaluation by highlighting the training—context interaction the temporal nature of training effects. A follow up study evaluating longer term G-AP implementation is underway.